Establishment of feijoa (Acca sellowiana) callus and cell suspension cultures and identification of arctigenin - a high value bioactive compound - Raikar, Sanjeev V.; Isak, Ilena; Patel, Sunita; Newson, Harriet L.; Hill, Stefan J. (Frontiers in Plant Science, 2024)
Feijoa (Acca sellowiana (O. Berg.) Burret), also known as pineapple guava, is a member of the Myrtaceae family and is well known for its fruit. Chemical profiling of the different tissues of the feijoa plant has shown that they generate an array of useful bioactive compounds which have health benefits such as significant antioxidant activities. In this study, an in vitro culture system has been developed, which could be explored to extract high-value bioactive compounds from feijoa. Feijoa tissue culture was initiated by the induction of callus from floral buds. Sections of floral buds were plated on MS medium supplemented with 2,4-D and BAP at 2.0mg/L and 0.2mg/L concentrations, respectively. Cell suspension cultures of feijoa were established using a liquid MS medium with different concentrations of 2,4-D and BAP and cultured on a rotary shaker. The growth of the cell suspension was evaluated with different parameters such as different carbohydrate sources, concentration of MS media, and inoculum density. When the cell suspensions were treated with different concentrations of MeJA at different time points, phytochemicals UPLC -QTOF MS analysis identified extractables of interest. The main compounds identified were secondary metabolites (flavonoids and flavonoid-glucosides) and plant hormones. These compounds are of interest for their potential use in therapeutics or skin and personal care products. This report investigates essential methodology parameters for establishing cell suspension cultures from feijoa floral buds, which could be used to generate in vitro biomass to produce high-value bioactive compounds. This is the first study reporting the identification of arctigenin from feijoa, a high-value compound whose pharmaceutical properties, including anti-tumour, anti-inflammatory and anti-colitis effects, have been widely reported. The ability of feijoa cell cultures to produce such high-value bioactive compounds is extremely promising for its use in pharmaceuticals, cosmeceuticals and nutraceuticals applications.